Legislative Deficiencies in Addressing Artificial Intelligence Crimes - Nasrallah Saad, Lect .Dr. Eid (Basra studies journal, 2025)
This research aims to propose new criminal legislative mechanisms to address crimes involving artificial intelligence, given that scientific and technological advancements have evolved both the form and concept of crime. Accordingly, the study examines the concept of artificial intelligence and its significance in the criminal field through various dimensions, including: criminal profiling, criminal justice applications, predicting terrorist attacks, locating suspects, forecasting crime rates, reconstructing crime events, and employing AI technologies in criminal investigation processes. Despite the numerous advantages of artificial intelligence, certain risks arise regarding its misuse in committing crimes, such as cyber-terrorism and deepfakes—considered among the most dangerous technological threats facing human societies in the digital era. Therefore, combating these crimes domestically requires proactive policing and preventive security measures, for which the use of AI technologies is highly recommended. Artificial intelligence–related crimes can also be addressed by imposing appropriate criminal penalties on natural persons who commit such offenses, in accordance with the Penal Code, as well as penalties suitable for legal persons consistent with their nature and legal standing. On the international level, combating these crimes necessitates global cooperation based on the principle of extradition, whether the offenses involve AI or other types of crime. The research concludes with a summary of key findings and several recommendations intended to support future legislative reforms.